Path Analysis in the Application of Occupational Health and Safety in the Ship Machinery Laboratory - Ningrum Astriawati; Waris Wibowo; Prasetya Sigit Santosa; Benny Hartanto; Yudhi Setiyantara (Postgraduate, University of Mataram, 2023)
This study aims to analyze the influence of learning attitudes, learning knowledge and learning motivation on the Application of Occupational Health and Safety using path analysis. The method used in this study is the quantitative method with a correlational research type. The population in this study is cadets of the Ship Machinery Study Program, at Yogyakarta Maritime High School. Sample The selection of research samples is carried out using the saturated sampling method or census method, which is all members of the sample population. The data analysis method uses path analysis with the Smartpls3 SEM model. Based on the results of the study, there was a significant positive direct influence of learning attitudes on the learning motivation of cadets. Learning attitudes have a positive and significant effect on the Application of Occupational Health and Safety (OHS) in the Ship Machinery Laboratory. Furthermore, there is a significant positive direct influence of learning knowledge on the learning motivation of cadets. Learning knowledge has a positive and significant effect on the Application of Occupational Health and Safety (OHS) in the Ship Machinery Laboratory. Learning motivation has a positive and significant effect on the Application of Occupational Health and Safety (OHS) in the Ship Machinery Laboratory.